2013
DOI: 10.1590/s0102-86502013001300012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbaric oxygen therapy on liver function during intermittent ischemia

Abstract: PURPOSE:To analyze the effects of hyperbaric oxygen therapy on liver function in rats previously subjected to ischemia and reperfusion. METHODS: A randomly distribution of 23 Wistar rats was conducted into three groups: SHAM, animals subjected to surgical stress without restricting blood flow by clamping the hepatic pedicle, IR, rats underwent hepatic vascular occlusion intermittently for two complete cycles of 15 minutes of ischemia followed by 5 min of reperfusion, IR / HBO, rats underwent hepatic pedicle cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
5
2
Order By: Relevance
“…Although expected, no difference was observed with HBO. This fact was not observed in other studies, in which the SHAM and IR groups already presented some difference [10][11][12]16 . In those studies there was an increase in the rate of oxygen consumption by the mitochondria compared to the SHAM group in order to maintain the electrochemical proton gradient on the mitochondrial membrane so that the membrane would be able to phosphorylate ADP 16,17 .…”
Section: Discussioncontrasting
confidence: 78%
“…Although expected, no difference was observed with HBO. This fact was not observed in other studies, in which the SHAM and IR groups already presented some difference [10][11][12]16 . In those studies there was an increase in the rate of oxygen consumption by the mitochondria compared to the SHAM group in order to maintain the electrochemical proton gradient on the mitochondrial membrane so that the membrane would be able to phosphorylate ADP 16,17 .…”
Section: Discussioncontrasting
confidence: 78%
“…In the present study, with respect to MDA, we observed a tendency to an increase of ROS in the I/R group, which was aggravated in the HBO-I/R group, demonstrating a lack of protection, as also reported in other studies 9,10,19 .…”
Section: Discussionsupporting
confidence: 89%
“…No significant improvement occurred in AST levels, with no significant difference between the groups submitted or not to HBO, and with the levels of both groups being higher than those of the control group. This leads us to question the hepatoprotective effect of hyperoxic preconditioning, which is supported by some authors and contested by others 9,10,19,20 .…”
Section: Discussionmentioning
confidence: 98%
“…This result is found by other authors 12,13 , but in different models of ischemia-reperfusion. Taking into consideration the oxygen consumption in stage 3 it was not found in our study significant difference between the group that underwent ischemia and, reperfusion with or without exposure to HBO, demonstrating that HBO was not harmful when this parameter was evaluated.…”
Section: Discussionsupporting
confidence: 88%
“…The use of HBO in the I/R damage is controverse, because it was believed that its use would increase tissue damage by raising the level of oxygen and consequently the level of reactive species and free radicals in the blood. However, there are studies that show positive changes caused by its use, suggesting a protective effect in different tissues [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%